Decentralized matching markets : a laboratory experiment - Pais, Joana (2012)
We report data from controlled laboratory experiments on two-sided matching markets in which participants interact in a decentralized way, without having to refer to a central clearinghouse. Our treatments have been designed to evaluate the effect of information, search costs, and binding agreements on the final outcome and also on the individual strategies that lead to it. We find that these features affect the level and pace of market activity as well as the identity of those who receive proposals. While the lack of information alone does not reduce stability or efficiency, its combination with search costs can be detrimental.